PENGEMBANGAN KULINER LOKAL SEBAGAI DAYA TARIK WISATA DI DILI, TIMOR LESTE - Barreto Araujo, Elizabeth (Jurnal Master Pariwisata (JUMPA); Volume 03, Nomor 01, Juli 2016, 2016)
The development of tourism industry can provide opportunities for tourism products including culinary in Dili, Timor-Leste. This article aims to identify types of traditional foods, measure the perception of tourists on traditional food and formulate program to develop traditional food as culinary tourism. Data collection for this article used direct field observation, interviews and documentation study, while data analysis used SWOT matrix. The results of this article revealed that in Dili there were several types of traditional food such as Saboko, Tukir, Kulu tunu or Kulu Gisa could be developed as culinary tourism. In regard to tourist perception on traditional food processing while good on quality of traditional food, food cleanliness and quality of restaurant service. Several programs conducted by the government to develop traditional food are human resource quality improvement, creating market for traditional food, identification of potential local products in each district and assessment of traditional foods.The restaurant owners also develop several programs such as menu adjustment, creativity in traditional food processing, and promotion.
Keywords: development, traditional food, attraction, culinary tourism, Timor Leste.